The Effect of Digital Literacy, Innovative Work Behavior, and Interpersonal Communication on Teachers Performance at Madrasah Aliyah - Wasis Dewanto; Encep Syarifudin; Sholeh Hidayat (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Education has a crucial role in the advancement of a country. The disparity in the quality of education can be attributed not only to the educational process, but also to the subpar performance of teachers as educators. The objective of this study is to ascertain the impact of digital literacy, innovative work behaviour, and interpersonal communication on teacher performance. This study use statistical survey methodology to authenticate its conclusions. The Partial Least Squares Structural Equation Model (PLS-SEM) was employed by the researchers. The Serang City area in Indonesia is home to a collective of 19 public elementary schools. The research sample comprised 19 school administrators and 81 state elementary school teachers in Serang City, Banten, Indonesia. We implemented the sampling process using a stochastic technique. PLS path modelling is employed in data analysis. The research findings indicate a significant impact of innovative work behaviour, digital literacy, and interpersonal communication on teacher effectiveness, with a p-value of less than 0.05 for each relationship. The research findings hold considerable ramifications for school principals seeking to enhance teacher effectiveness.